2015
DOI: 10.1021/acsami.5b03672
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dot Layers with Energy-Down-Shift Effect on Crystalline-Silicon Solar Cells

Abstract: Graphene quantum dot (GQD) layers were deposited as an energy-down-shift layer on crystalline-silicon solar cell surfaces by kinetic spraying of GQD suspensions. A supersonic air jet was used to accelerate the GQDs onto the surfaces. Here, we report the coating results on a silicon substrate and the GQDs' application as an energy-down-shift layer in crystalline-silicon solar cells, which enhanced the power conversion efficiency (PCE). GQD layers deposited at nozzle scan speeds of 40, 30, 20, and 10 mm/s were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…After the depositon of GQDs, an enhancement of 2.94–6.1% and 2.7–14.9% has been observed in J SC and η of Si solar cells, respectively. The enhanced performance in Si solar cells was explained by the energy-down-shift effect due to GQDs12. In our opinion, the carrier injection from GQDs should also play a role in the enhanced conversion efficiency in the GQD-deposited Si solar cells since GQDs exhibit a lower work function (~3.7 eV) than that of Si (4.2 eV)13.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…After the depositon of GQDs, an enhancement of 2.94–6.1% and 2.7–14.9% has been observed in J SC and η of Si solar cells, respectively. The enhanced performance in Si solar cells was explained by the energy-down-shift effect due to GQDs12. In our opinion, the carrier injection from GQDs should also play a role in the enhanced conversion efficiency in the GQD-deposited Si solar cells since GQDs exhibit a lower work function (~3.7 eV) than that of Si (4.2 eV)13.…”
Section: Resultsmentioning
confidence: 76%
“…Other semiconductor solar cells could improve their conversion efficiency by using GQDs as well. Recently, performances of Si solar cells have been investigated by depositing GQDs on the surface of Si solar cells1112. After the depositon of GQDs, an enhancement of 2.94–6.1% and 2.7–14.9% has been observed in J SC and η of Si solar cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if E ph is larger than E g (as in the case of UV light), the photons are absorbed, but the excess energy ( E ph – E g ) is not used effectively for generation of photocurrent, and it causes electron thermalization. 35 As discussed earlier, the value of ESM characterizes the overlap between the emission band of LDS material and the EQE band of the used PC. In the present study, the value of ESM for the green luminescent N-GQD3 is found to be 4 times higher than that of direct UVA radiation (Table 1 and Figure 6b).…”
Section: Resultsmentioning
confidence: 97%
“…29,30 Optical, electrical, thermal and mechanical properties of such QDSLs are thus determined not only by individual QDs, but also by the dimensionality dependent resonant couplings through the interior nano space among adjacent QDs tuned by ligand engineering down to subnanometer regime. 3,14,19,[31][32][33][34][35][36][37][38] Thus, the dimensionality in the QDSLs should be a crucial parameter for independent tailoring of the electronic and photoexcited properties including the multiple exciton generation (MEG) through which multiple electron-hole pairs can be produced; [39][40][41] the MEG is expected to increase solar cell efficiency by creating multiple carriers from a single photon absorption. 42 Meanwhile, temperature can be another important parameter to control the physical properties of the QDSLs.…”
Section: Introductionmentioning
confidence: 99%